Improving Student Learning Outcome-Based Archiving Module Development through Guided Inquiry / Meningkatkan Hasil Belajar Siswa Melalui Pengembangan Modul Kearsipan Berbasis Guided Inquiry - Ika Purwanti (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
This module is integrated with guided inquiry model in order to improve the learning process that support students’ thingking ability development. The product developed is Filling Management learning module on the subject of filling system using guided inquiry model. Module validation is done by a lecture of department of management in office administration major of State University of Malang, a teacher on the subject of filling system at SMK PGRI 2 Malang and ten students of the tenth grade of SMK PGRI 2 Malang. The result of the validation shows that the modul is categorized as very valid. The average persentage of the validation result is 93%. This module is effective to improve the quality of learning processes and achievement, referring to the difference of the mean scor of students achievement of experimental class and the controlled class that is 73,767 and 59,674 using t test in SPSS program. The further is suggested to use this module based on guided inquiry as an alternative to support the learning of Filling Management in the subject of filling system.ABSTRAK: Modul ini diintegrasikan dengan model guided inquiry yang bertujuan untuk mengembangkan kemampuan proses berpikir siswa. Produk pengembangan adalah modul pembelajaran Kearsipan pada materi sistem kearsipan menggunakan model guided inquiry. Validasi modul dilakukan oleh 1 orang dosen jurusan manajemen program studi administrasi perkantoran Universitas Negeri Malang, 1 orang guru mata pelajaran Kearsipan di SMK PGRI 2 Malang, dan 10 siswa kelas X SMK PGRI 2 Malang. Hasil validasi menunjukkan bahwa modul termasuk kategori sangat valid. Hasil persentase rata-rata uji validasi adalah 93%. Modul ini efektif digunakan untuk meningkatkan kualitas proses dan hasil belajar, ditinjau dari perbedaan rata-rata hasil belajar kelas eksperimen dengan kelas kontrol, yaitu 73,767 dan 59,674 melalui uji t program SPSS. Lebih lanjut disarankan untuk menggunakan modul berbasis guided inquiry ini sebagai alternative penunjang pembelajaran Kearsipan pada materi sistem kearsipan.